Preparo e caracterização de material de referência de solo para nutrientes e contaminantes inorgânicos - Verhalen, Tatiane Rosane (2014)
The certified reference materials make an important role in the establishment of traceability in analytical chemistry, ensuring reliability and accuracy to the measurements and are fundamental for the validation of analytical methods. The demand for new certified reference materials increases in all areas of knowledge, with emphases to the agriculture. Basis for the production of farming products, the demand for soil analysis is great and the existence of a reference material of a typical Brazilian soil is important to ensure the quality of results. In this context, the present work describe the preparate and the characterization of a national reference material for Cr, Pb, Cd, and As soil contaminants and Ca, P, Mg, K, Cu, Fe, Mn, Zn, and Na macro and micronutrients. The material was produced following the internationally accepted ISO Guides 30-35 norms considering the preparation and packaging, homogeneity, short and long term stability, and material characterization and certification. A Typic Paleudult soil was artificially contaminated with As, Cd, Cr, and Pb, added as salt solutions from Pb(NO3)2; Cd(NO3)2.4H2O; Na2HAsO4.7H2O, and Cr(NO3)3.9H2O salts. After 12 month of contamination, 65 kg of soil was dried at room temperature, ground (particles size < 390μm), homogenized, packaged and irradiated with gamma ray (20 - 25 kGy) aiming to increase the shelf-life. The analyte soil extractions were based on methodology recommended by Brazilian legislation (CONAMA N° 420), with in turn follows the protocol established by American environmental agency (USEPA 3051). It was performed by assisted microwave oven with the use of 14 mol L-1 HNO3. The evaluation of the estimate minimum amount, homogeneity and stability of the material were carried out, using inductively coupled plasma optical emission spectroscopy (ICP OES) determination technique. The results were submitted to analysis of variance of single factor (ANOVA). The homogeneity and stability of the material presented means within a confidence interval of 95% for As, Cd, Pb, Cr, Ca, Cu, Fe, Na, K, Mg, Mn, and P. The chemical characterization of the material was performed through a collaborative test and the uncertainties related to each step of the material prepare were calculated to obtain the expanded uncertainty for each one of the analytes and to the final drafting of the control chart with the results of the reference material.